2020
DOI: 10.1001/jamaneurol.2020.1179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Treatment Strategies for Medication Overuse Headache

Abstract: IMPORTANCE Medication overuse headache (MOH) is a disabling, globally prevalent disorder representing a well-known and debated clinical problem. Evidence for the most effective treatment strategy is needed.OBJECTIVE To compare 3 treatment strategies for MOH. DESIGN, SETTING, AND PARTICIPANTSThis open-label, randomized clinical trial with 6 months of follow-up was conducted in the tertiary sector at the Danish Headache Center, Glostrup, from October 25, 2016, to June 28, 2019. Of 483 patients with MOH referred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 34 publications
3
91
2
3
Order By: Relevance
“…During the pandemic, we found few MOH patients experiencing improved headache days and intensity compared with pre-pandemic period. These results differ from the findings of several published studies conducted in MOH patients under non-COVID-19 condition [ 14 , 17 , 31 , 32 ], which found significant decrease in headache days and intensity per month in most MOH patients with regular prophylactic medications. The inconsistency is probably due mainly to the difficulty of accessing to regular prophylactic medications during the pandemic on basis of our analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…During the pandemic, we found few MOH patients experiencing improved headache days and intensity compared with pre-pandemic period. These results differ from the findings of several published studies conducted in MOH patients under non-COVID-19 condition [ 14 , 17 , 31 , 32 ], which found significant decrease in headache days and intensity per month in most MOH patients with regular prophylactic medications. The inconsistency is probably due mainly to the difficulty of accessing to regular prophylactic medications during the pandemic on basis of our analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…However, while some studies report high “cure” rates with complete cessation of acute medications, most patients require the addition of preventive treatment to successfully stop or reduce the overused medication(s) (22). In a head-to-head comparison of three differing treatment modalities, data from several secondary endpoints indicated that withdrawal of acute medication combined with prophylactic treatment was more effective than either treatment alone (9). The data from this post hoc analysis indicate patients with medication overuse, who were not weaned off or instructed to limit the use of acute medications, responded to galcanezumab equally as well as patients without medication overuse.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic review of different treatment strategies for medication overuse headache concluded that adding preventive medication to the withdrawal of overused medications led to better improvements than early discontinuation alone (8). More recently, a randomized clinical trial that directly compared treatment modalities found withdrawal of acute medication in combination with initiating preventive medication constituted a more effective treatment for medication overuse headache than either approach alone (9).…”
Section: Introductionmentioning
confidence: 99%
“…The headache pattern becomes clearer during withdrawal, and a correct diagnosis would help find the best treatment option for preventive medication; 2) It seemed that some patients did not need preventives after withdrawal. However, a recently Danish study has reported that early start of preventive medication simultaneously with start of withdrawal therapy is more effective in treating MOH, compared to a strategy where preventive treatment is postponed to after withdrawal [57]. This may be due to fewer patients starting preventive medication when assigned to the last-mentioned strategy.…”
Section: Preventive Medication For Mohmentioning
confidence: 99%
“…However, a recently Danish study has reported that early start of preventive medication simultaneously with start of withdrawal therapy is more effective in treating MOH, compared to a strategy where preventive treatment is postponed to after withdrawal [ 57 ]. This may be due to fewer patients starting preventive medication when assigned to the last-mentioned strategy.…”
Section: Medication Overuse Headachementioning
confidence: 99%